PENGARUH RETURN ON ASSETS (ROA), NON PERFORMING LOAN (NPL), DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PERTUMBUHAN LABA (Studi pada PT BPR Cianjur periode 2007-2016) - Muhammad Ali (Universitas Widyatama, 2018)
The purpose of this study is determining how much influence of Return On Assets (ROA), Non-Performing Loan (NPL) and Capital Adequacy Ratio (CAR) either partially or simultaneously toward of Earnings Growth at PT BPR Cianjur in period 2007-2016. The methods used in this research are descriptive and associative methods. To determine the influence of these variables used multiple linear regression analysis. And then doing hypothesis test of partial t test and F test of simultaneously using application software SPSS 22. The Result of this study shows an average of the year 2007-2016 from Return on Assets (ROA) amounted to 4,4230, Non-Performing Loan (NPL) amounted to 7,6630, Capital Adequacy Ratio (CAR) amounted 35,2110, and Earnings Growth amounted 22,20. Based upon the research, there is results that Return On Assets (ROA), Non-Performing Loan (NPL) is not significant on Earnings Growth, and Capital Adequacy Ratio (CAR) has a positive significant effect on Earnings Growth. The simultaneous Return On Assets (ROA), Non-Performing Loan (NPL) and Capital Adequacy Ratio (CAR) significantly effects on Earnings Growth.